II Encuentro Nacional de Técnicos y Tecnólogos en Estomatología - Niovis Pedro Garro (Editorial Ciencias Médicas, 2017)
The II National Meeting of Technicians and Technologists in Dentistry took place on October 5, 2016, at the Quinta de los Molinos, legendary center for scientific activities in the capital of Havana, Cuba. He had the coauspicio of the Cuban Society of Stomatology and the participation of 46 delegates from various provinces of the country. The MSc presided over the activity. Lic. Orialis Ramos Leliebre, Lic. Niovis Pedro Garro and Lic. Marlene María Macias Travieso. One of the emotional moments of the meeting was when the MSc. Dr. María Rosa Sala, referred to Dr. Orlando de Cárdenas Sotelo and founding members of the National Group of Promotion and Education for Health in Stomatology, to mark the 27th anniversary of its founding. Various topics were included in the meeting, including: communication, educational techniques and teaching methods, educational strategy for the development of the preventive competence of the oral health team in oral diseases, basic elements of epidemiology in stomatological practice, use of educational messages in support of health promotion activities, health experience from intersectoral practice, oral hygiene education strategy in primary schools; all with a common thematic axis "Promotion and Education for Health," as a way to raise awareness and quality of life of the population, addressed through conferences, posters and round table. They highlighted the following presentations: - Round table in which participants were exposed in a participatory and creative way, essential tools to develop the Promotion and Education for Health in various scenarios, in order to promote a healthy environment, developed by the MSc. Dra María Rosa Sala Adam, MSc. Lic Ana Cepero Gil, moderated by Lic. Niovis Pedro Garro.     The Conference on basic aspects of Epidemiology, which led to the reflection on daily practice in stomatological services, provided by the MSc. Dr. Ileana Frómita Suárez.     The conferences on educational strategies proposals of the MSc. Lic. Orialis Ramos Leliebre and the complementary edges, both in the preventive competence of the oral health team, and in the improvement of oral hygiene in the primary education of Lic. Niovis Pedro Garro. Another interesting moment was the conference "Health experience from intersectoral practice" of Dr. Leyssan Cepero Fiallo. In addition, traditional posters were exhibited, in which the students of the Stomatological Care Technician of the Faculty of Medical Sciences "Victoria de Girón", Lisandra Ortega Fernández, Adriana María Rodríguez Guillót and her MSc teacher. Lic. Carmen Gloria Valverde, showed creativity. Some provinces sent their educational experience by email; among them Cienfuegos, Mayabeque and Guantánamo. In the words of the participants, the meeting was enriching, due to the variety in the topics discussed and the possibility that the delegates had to spontaneously express their experiences and motivations of their daily work.